Conservation of Glomerular Organization in the Main Olfactory Bulb of Anuran Larvae - Weiss, Lukas; Jungblut, Lucas D.; Pozzi, Andrea G.; O’Connell, Lauren A.; Hassenklöver, Thomas; Manzini, Ivan (Frontiers in Neuroanatomy, 2020)
The glomerular array in the olfactory bulb of many vertebrates is segregated into molecularly and anatomically distinct clusters linked to different olfactory functions. In anurans, glomerular clustering is so far only described in Xenopus laevis. We traced olfactory projections to the bulb in tadpoles belonging to six distantly related anuran species in four families (Pipidae, Hylidae, Bufonidae, Dendrobatidae) and found that glomerular clustering is remarkably conserved. The general bauplan consists of four unequally sized glomerular clusters with minor inter-species variation. During metamorphosis, the olfactory system undergoes extensive remodeling. Tracings in metamorphotic and juvenile Dendrobates tinctorius and Xenopus tropicalis suggest a higher degree of variation in glomerular organization after metamorphosis is complete. Our study highlights, that the anatomical organization of glomeruli in the main olfactory bulb is highly conserved, despite an extensive ecomorphological diversification among anuran tadpoles, which suggests underlying developmental constraints.